What Expert Say about Routine Exercises and Living Expectation in Pandemic Times (Analysis of Health Literature) - Widjaja, Gunawan; Sijabat, Hotmaria Hertawaty (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aimed to understand whether exercise, particularly fast walking in the open, as an activity, affects life expectancy; in other words, it reduces the risk of early death among the older generation. This research study took data on papers published in 10 years from 2010 to 2020. It consists of 50 paper titles from various international study contexts. Our exploration is limited to secondary data that we search with the help of the internet from databases of international publications such as Google Books, Elsevier, Taylor&France, and Sagepub. Next, we analysed using a phenomenological approach involving a coding system, evaluation, and in-depth interpretation before making conclusions that will make valid and reliable finding data. The records of the existence of findings from the 50 articles that we reviewed were collected. We found that daily exercise and fast walking had the opposite connection to mortality or more extended life expectancy in general. The data has controlled for various factors such as age and health status. We found that those with a background characterized by being physically active had a reduced risk of death than those who did not participate in daily fast walking.